Apoyo en los procesos y desarrollo de las labores de emplazamiento preventivo, correctivo y puesta a punto de un sistema fotovoltaico on grid, off grid e hibrido en la Compañía Energysoft S.A.S Ibagué – Tolima. (2020)
This document describes the steps that were taken during the business management, in the area of design and location of a photovoltaic system on grid, off grid and hybrid in the Energysoft S.A. Company Ibagué - Tolima. The main objective proposed in this project, was oriented in the approval of processes and in the development of preventive, corrective siting and tuning of a photovoltaic system, governing under the standards, parameters and functions established by the company, in each one of the industries of the poultry, agronomist and industrial sector, where the projects were carried out. This business management was also focused on the application of all the knowledge acquired by the intern Juan Pablo Bernal Mora, regarding the training processes as a professional in electronic engineering and the additional knowledge acquired through the skills provided by the company. As described above, the intern was part of the planning of these photovoltaic systems, dividing his work into two opposite methods: the first, was carried out through work carried out in the office, focused on design planning, creating plans and material cubing; The second method was carried out by means of field work, focused on the interpretation of plans and the location of photovoltaic solar plants. Initially, a survey of the areas was carried out, taking into account all the corresponding technical criteria for the location of the photovoltaic systems.